Sleep restriction alters plasma endocannabinoids concentrations before but not after exercise in humans. (December 2016) - Cedernaes, Jonathan; Fanelli, Flaminia; Fazzini, Alessia; Pagotto, Uberto; Broman, Jan-Erik; Vogel, Heike; Dickson, Suzanne L.; Schiöth, Helgi B.; Benedict, Christian
Highlights: Sleep restriction increases plasma endocannabinoids levels. Sleep restriction does not alter exercise-induced release of endocannabinoids. Sleep restriction increases hunger and decreases stress feelings. Abstract: Following binding to cannabinoid receptors, endocannabinoids regulate a variety of central nervous system processes including appetite and mood. Recent evidence suggests that the systemic release of these lipid metabolites can be altered by acute exercise and that their levels also vary across the 24-h sleep-wake cycle. The present study utilized a within-subject design (involving 16 normal-weight men) to determine whether daytime circulating endocannabinoid concentrations differ following three nights of partial sleep deprivation (4.25-h sleep opportunity, 2:45–7 a.m. each night) vs . normal sleep (8.5-h sleep opportunity, 10:30 p.m.–7 a.m. each night), before and after an acute bout of ergometer cycling in the morning. In addition, subjective hunger and stress were measured. Pre-exercise plasma concentrations of 2-arachidonoylglycerol (2AG) were 80% higher 1.5 h after awakening ( vs . normal sleep, p < 0.05) when participants were sleep-deprived. This coincided with increased hunger ratings (+25% vs . normal sleep, p < 0.05). Moreover, plasma 2AG was elevated 15 min post-exercise (+44%, p < 0.05). Sleep duration did not however modulate this exercise-induced rise. Finally, subjective stress was generally lower on the day after three nights of short sleep vs . normal sleep, especially after exercise (p < 0.05). Given that activation of the endocannabinoid system has been previously shown to acutely increase appetite and mood, our results could suggest that behavioral effects of acute sleep loss, such as increased hunger and transiently improved psychological state, may partially result from activation of this signaling pathway. In contrast, more pronounced exercise-induced elevations of endocannabinoids appear to be less affected by short sleep duration.